Uganda : Second Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria-Staff Report; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Uganda. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
Uganda showed strong macroeconomic stability under the Poverty Reduction and Growth Facility (PRGF) Arrangement. Executive Directors welcomed this development as well as the fiscal adjustment. They stressed the need for strengthening their policies for boosting economic growth and reducing poverty in the context of the Poverty Eradication Action Plan. They emphasized the need to strengthen monetary, fiscal, and exchange rate policies, accelerate structural reforms, and restructure the Uganda Development Bank Limited. They agreed that Uganda has successfully completed the second review under the PRGF Arrangement, and approved waiver.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet